Housing Conditions of Migrant Workers from Central Asia in Russia - Dmitry V. Poletaev (Население и экономика)
The aim of this study is to identify factors influencing the housing conditions of migrant workers from Central Asia in Russian cities, based on the author’s research conducted in 2023, 2020, and 2017 in Moscow, St Petersburg, and Yekaterinburg. The study encompasses 2.500 migrant workers from Tajikistan, Kyrgyzstan, and Uzbekistan. The findings indicate that the Russian rental housing market exhibits discriminatory practices towards foreigners, resulting in living conditions that differ significantly from those of Russian citizens. A substantial number of migrant workers are compelled to make informal payments for registration. The study shows that labour migrants from Tajikistan, Kyrgyzstan, and Uzbekistan tend to live in overcrowded conditions, with a high proportion (up to half) continuing to share accommodation with others (compatriots, friends, etc.). However, residence at the workplace is becoming increasingly uncommon. The analysis reveals a gradual increase in the proportion of migrant workers renting separate housing for themselves and their families. This trend is largely driven by the rising number of women from all three countries who rent housing either for individual residence or for cohabitation with relatives. The study also highlights persistent gender-based differences in the housing conditions of migrant workers from Tajikistan, Kyrgyzstan, and Uzbekistan in Russia. The hypothesis that female migrant workers from these countries generally experience more comfortable housing conditions was confirmed.